PENGEMBANGAN ALAT EVALUASI PEMBELAJARAN IPA YANG MENDUKUNG KETERAMPILAN ABAD 21 - Agus Ramdani; A. Wahab Jufri; Gunawan Gunawan; Saprizal Hadisaputra; Lalu Zulkifli (Jurnal Penelitian Pendidikan IPA, 2019)
This study aims to develop learning devices, especially in the evaluation section of science learning in junior high school, which in turn after being implemented in the classroom is expected to develop 21st century skills of students. In particular, this study aims to, 1) identify science learning evaluation tools made by teachers so that they obtain a clear picture of the profile of the evaluation tool, 2) develop a junior high school science learning evaluation tool that supports 21st century skills. This research includes development research in four stages, namely: decide, design, develop, and evaluate. The results of this study indicate that the tools developed by the teacher are in complete category, the learning objectives are clear, although the stages in part still need to be improved. Learning evaluation instruments developed by the teacher have met the principles of assessment, the presentation is in accordance with the curriculum, the sentence in the question is quite communicative, uses good and correct language and does not cause multiple interpretations. However, the majority of questions made by teachers still measure low-level thinking skills. This is because teachers have not been trained in developing questions that measure high-level thinking skills. An evaluation tool that was then developed together with the teacher was intended to perfect the shortcomings of the previous evaluation toolKeywords: 21st Century Skills, Learning Evaluation Tools, Middle School Science